The heteroatom effect in ambipolar diradicals. - Moles Quintero, Sergio; Harbuzaru, Alexandra; Marín-Beloqui, José Manuel; González Núñez, Raúl; Ponce-Ortiz, Rocío; Casado-Cordón, Juan (My University, 2023)
The ability to efficiently transport both holes and electrons makes ambipolar organic materials appealing architectures in organic electronics for the development of p- and n-channel devices. However, most of the organic semiconductors do not exhibit ambipolar behaviour mainly due to their intrinsic electronic properties (energetic mismatch between their frontier molecular orbitals and the Fermi levels of the metals used as drain and source electrodes) and to charge trapping at OFET–gate dielectric interfaces. The search of new ambipolar materials is closely related to the examination of the redox amphoterism in π-conjugated structures, i.e., the capacity to equally accommodate positive and negative charges. In this context, the small HOMO-LUMO gap of π-conjugated molecules showing an incipient or medium diradical character makes them good candidates to display p–n balanced mobilities. Several open-shell molecules, such as a diindeno[b,i]anthracene derivative, zethrenes and diindenoperylenes, have been reported as efficient ambipolar materials indeed. In this communication we present a series of four difluorenoheteroles (DFX) with identical chemical structure except for the role of the heteroatom which is played by Oxygen, Nitrogen, Sulphur and Sulphur dioxide. The entire DFX series exhibit a medium diradical character as consequence of the combination of electronic affinity, captodative effect and aromatic stabilization. Addressing the electronic properties of the neutral, reduced and oxidized species of the DFX family we demonstrate their ambipolar electrical behaviour and elucidate the connection between their diradical character and the balance between the electron and hole transport.
Contribución tipo Póster con Flash oral
Keywords: Compuestos orgánicos; Ambipolar diradicals; OFET